Women Survivors of Adolescent Dating Violence Describe the Maintenance of Their Abusive Relationships: First Person Stories via YouTube. (April 2023) - Hegel, Jennifer; Cummings, Jorden A.; Toews, Kelsi; Knowles, Laura A.; Willcott-Benoit, Whitney; Palermo, Alisia M.; Deleurme, Kendall A.
The current study explores the personal stories of young women on their own experiences with adolescent dating violence and focuses on their perceptions of the relevant factors that maintained the relationship over time. To this end, we analyzed seven publicly available videos on YouTube of women explaining their experiences of adolescent dating violence, including how they perceived their relationships to be maintained over time. We identified four major sources these survivors perceived as contributing to the maintenance of adolescent dating violence: the Self, the Partner, the Relational Dynamic, and Other People.